HDSS: a healthcare decision support system on combining domain knowledge and data analytics for predicting potential risk of mental health. (12th May 2022) - Ngan, Chun-Kit; Paat, Yok-Fong; Green, Rachel
We develop an HDSS to determine if a patient is at risk of mental health (MH) problems. This HDSS combines the strengths of both domain experts' knowledge and data analytics techniques to conduct the risk identification for patients. Our contributions are three-fold: 1) develop a two-tier hybrid-based prediction process to construct a classification model to predict if a person suffers from a particular symptom; and then determine if that person is at risk of suffering from MH problems based upon the domain experts' diagnostic criteria; 2) execute experiments to show that our approach is more effective and produces the results that are slightly less accurate than those of domain experts' diagnostic criteria but superior to those of the data analytics approach; 3) develop a dashboard that delivers descriptive visuals from diverse perspectives to assist physicians in obtaining a more comprehensive view of patients' MH status to provide them with better treatment and support.